Confucianism and legalism about the phenomenon of power (Journal of Philosophy Culture and Political Science, 2024)
: This article examines the conceptual differences and similarities in the teachings of Confucius and Lao Tzu regarding the phenomenon of power. The research is based on the analysis of the primary sources: Confucius and Lao Tzu, in order to identify their philosophical views on the nature, function and principles of power in government. The key texts of Confucius and Lao Tzu are analyzed in detail, which allows a deeper understanding of their vision of power and governance.  The purpose of the article is a comparative analysis of the doctrine of power in Confucianism and the philosophical justification of despotic power in the ancient Chinese epic-political doctrine «fa jia» (in the Western tradition it is called legalism).  The study of the phenomenon of power in the philosophy of ancient China inevitably leads to the consideration of two key figures - Confucius and Lao Tzu. These thinkers offered different but complementary views on the nature of power and the governance of society.  Power, according to Confucius, should be based on the moral qualities of the ruler. A wise leader serves as an example for his subjects, establishing stability and harmony. Confucius argued that the moral self-improvement of a leader is the basis for the legitimacy of his authority.  The Legists argued that optimal control is achieved through minimal intervention. The ruler should allow natural processes to occur smoothly, avoiding excessive control and coercion. Softness and fluidity are more important than strength and rigidity.        Both Confucians and legists alike considered the relationship of man, society and the state. They considered hierarchy to be the principle of this ratio. At its top is the state headed by the ruler, the middle is occupied by society, and at the bottom is a person. A person belongs to society, and both of them belong to the state. The state belongs to the ruler (monarch). Thus, both Confucians and Legists recognized the same form of government as the only correct ones. Both also saw the ideal of a state structure in an exemplary manner. However, the understanding of the methods by which this order is achieved is fundamentally different between Confucians and Legists.  Key words: power, the phenomenon of power, legalism, Confucianism, the state, Moism, Confucius, Han Fei, Shan Yang.